The effectiveness of smoking cessation interventions for socio-economically disadvantaged women: a systematic review and meta-analysis - Hayes, Catherine (My University, 2022)
Introduction: This systematic review and meta-analysis assessed the effectiveness of smoking cessation interven- tions among women smokers in low socio-economic status (SES) groups or women living in disadvantaged areas who are historically underserved by smoking cessation services. Methods: A systematic literature search was conducted using MEDLINE (OVID), EMBASE, Cochrane, CINAHL, PsychINFO and Web of Science databases. Eligibility criteria included randomised controlled trials of any smoking ces- sation intervention among women in low SES groups or living in socio-economically disadvantaged areas. A random effects meta-analysis assessed effectiveness of interventions on smoking cessation. Risk of bias was assessed with the Cochrane Risk of Bias tool. The GRADE approach established certainty of evidence. Results: A total of 396 studies were screened for eligibility and 11 (6153 female participants) were included. Seven studies targeted women-only. 5/11 tested a form of face-to-face support. A pooled effect size was estimated in 10/11 studies. At end of treatment, two-thirds more low SES women who received a smoking cessation intervention were more likely to stop smoking than women in control groups (risk ratio (RR) 1.68, 95% CI 1.36–2.08, I2= 34%). The effect was reduced but remained significant when longest available follow-up periods were pooled (RR 1.23, 95% CI 1.04–1.48, I 2 = 0%). There was moderate-to-high risk of bias in most studies. Certainty of evidence was low. Conclusions: Behavioural and behavioural + pharmacotherapy interventions for smoking cessation targeting women in low SES groups or women living in areas of disadvantage were effective in the short term. However, longer follow-up periods indicated reduced effectiveness. Future studies to explore ways to prevent smoking relapse in this population are needed.
PUBLISHED
Keywords: Health disparities; Tobacco control; Behavioural; Cessation; Meta-analysis; Gender; Cancer; Inclusive Society; Health; Social exclusion